Utilização de escória de alto forno em massa argilosa para a produção de blocos de vedação - BEZERRA, Kate Thayane Santos (2019)
The objective of this work was to analyze the addition of blast furnace granulate in the microstructure and in the technological properties of the red ceramics to produce seal-ing blocks. Initially, the solutions were characterized as chemistry and mineralogical by x-ray diffusion (XRD) and by x-ray fluorescence (XRF). Soon after the chemical and mineralogical characterization of the thermal behavior of the plants was studied, through the thermogravimetric (TG) and differential (DTG) analyzes. After finishing a stage of mineral, chemical and thermal characterization, the first samples were col-lected in layers of 0, 5 and 10% by wt. of slag that were sintered at three different temperatures (900 and 1000 ° C). The technology properties were water absorption (AA) and three-point flexural strength (σ). The obtained results include a slag can be incorporated into the ceramic matrix, since, they were found in the rocks of the ex-pected pattern.